Maintaining a loving vigil : parents' lived experience of having a baby in a neonatal unit : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Nursing at Massey University - Murphy, Maureen (Massey University, 1997)
Technological aspects of preterm birth and the care of preterm infants are continually examined, yet the impact of the event on families, and particularly parents, has not received the same attention. A review of the nursing literature illustrated that there are very few published articles examining parents' experiences in a Neonatal Intensive Care Unit, and in particular the effect this has on parents as a couple. Most studies focus on the mother, and there are a small number specifically focusing on the father. This study sought to elicit the experience of both parents as a couple. This research used phenomenology to examine five couples' experiences following the births of their preterm infants and their subsequent care in a Neonatal Intensive Care Unit. Semistructured interviews were conducted with the parents as a couple. While each couple viewed the experience through their special lens, this study identified themes experienced by all the couples. They described a struggling-within-themselves in an attempt to face and survive the experience. The parents were living through a time-of-uncertainty, and talked about the factors that helped them, and those that made the ordeal more difficult. The three relationships the parents described as being essential were: with each other, with their baby and with significant others. Although their concern for their babies never left them, eventually the parents were able to move-from-fear and feel increasingly comfortable with their experience as they participated more and more fully in the care of their baby. The research examined the parents' loving vigil with their baby and demonstrated the need for neonatal nurses to provide supportive intervention to influence positively the parents' struggle through the ordeal.
Keywords: Infants (Premature) -- Hospital care -- Psychological aspects; Neonatal intensive care -- Psychological aspects; Parent and child